NURSING CARE MANAGEMENT WITH EXCELLENT SERVICE FOR MRS. R.D. WITH GOUT ARTHRITIS AT THE BINJAI ELDERLY SOCIAL SERVICES UNIT, SOCIAL AFFAIRS OFFICE OF NORTH SUMATRA PROVINCE IN 2025 - Tresiya Wulandari Br Sitorus; Erika; Meriana Siregar; Agus Rogabe Sihotang; Liony Lindsay Manurung; Fri Yanti Simatupang; Dewi Sartika Hutabarat (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Based on data from the World Health Organization (WHO) in 2019, the number of gout arthritis cases increased significantly, reaching 1,370 (or approximately 33.3) by 2023. The country with the highest recorded number of cases is the United States, where about 26.3% of the total population has been affected. In Indonesia, the majority of gout arthritis sufferers are men, with the most affected age group being those aged over 45 years (Syamsidar, 2023). According to the Kamus Besar Bahasa Indonesia (KBBI), gout (commonly called gaut) is a metabolic disease characterized by elevated levels of uric acid in the blood serum and the formation of sodium urate deposits in various body tissues, including joints and soft tissues. This condition is usually caused by impaired renal excretion of uric acid or excessive endogenous production. Without proper and effective treatment, gout can progress to more serious stages, such as chronic gout, tophus formation (hard deposits around joints), and even severe kidney dysfunction. These complications can significantly impact a patient’s quality of life, impair mobility, and cause persistent pain. The prevalence of gout arthritis in Indonesia has not been extensively studied, but data indicate that the prevalence of hyperuricemia (elevated levels of uric acid in the blood) in Indonesia ranges from 18.6% to 47.6%. Hyperuricemia is a major risk factor that can contribute to the development of gout, although not all individuals with high uric acid levels will develop the disease. This high prevalence suggests that gout and related uric acid disorders may be a significant public health concern in Indonesia, especially given the increasing number of cases related to lifestyle, dietary habits, and genetic factors (Safira & Tengah, 2022). in North Sumatra Province, the prevalence of arthritis diagnosed by healthcare professionals reached 8.4%, while based on diagnosis or self-reported symptoms, the figure increased to 19.2%. Meanwhile, in Medan City, the prevalence based on professional diagnosis was 5.1%, and when considering both diagnosis and symptoms, it rose to 17.2% (Hasibuan & Simamora, 2020)